Reporter Gene Imaging of Immune Responses to Cancer: Progress and Challenges - Purnima Dubey (Theranostics, 2012)
Immune responses to cancer are dynamic processes which take place through the concerted activity of innate and adaptive cell populations. In order to fully understand the efficacy of immune therapies for cancer, it is critical to understand how the treatment modulates the function of each cell type involved in the anti-tumor immune response. Molecular imaging is a versatile method for longitudinal studies of cellular localization and function. The development of reporter genes for tracking cell movement and function was a powerful addition to the immunologist's toolbox. This review will highlight the advances and challenges in the use of reporter gene imaging to track immune cell localization and function in cancer.